Pekanbaru Hallyu Culture Center dengan Pendekatan Arsitektur Dekonstruksi Menurut Frank O. Gehry - Yuri Prima Nurullah; Pedia Aldy; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Hallyu is a term given to the spread of Korean Pop culture and triggers many people in every country to learn both Korean language and culture. With the development of Hallyu, many Indonesian teenagers, especially in Pekanbaru city, formed communities related to Kpop. Their interest in things related to Hallyu itself such as fashion, film, drama, music and culinary. Therefore it needed a place that can accommodate the interests and talents oraccommodate the activities of hallyu communities and fans in a more complex place especially in the region of Pekanbaru which functioned as a center for korean contempory culture learning and reacreation/entertament. The design of Pekanbaru Hallyu Culture Center is done by combining the function with the principle approach of deconstruction and analyze the design characteristics of Frank O. Gehry. The concept used in this design is